Specific TLR4 Blocking Effect of a Novel 3,4-Dihydropyrimidinone Derivative - Zhou, Mingqian; Wang, Yiqi; Lin, Xiaoying; Wan, Jieping; Wen, Chengping (Frontiers in Pharmacology, 2021)
Background: Toll-like receptor 4 (TLR4) initiates both innate and adaptive immune responses, which plays an important protective role in self-defense mechanisms. Excessive or inappropriate TLR4 activation causes the development of many autoimmune diseases. Dihydropyrimidinone derivatives are medicinally important molecules with diverse pharmacological activities, including anti-inflammatory activity. The present study focused on novel synthesized 3,4-dihydropyrimidinone derivatives and evaluated their inhibitory effects on TLR4. Methods: A series of 3,4-dihydropyrimidinone derivatives were recently synthesized and evaluated for their TLR4 inhibition activities and cytotoxic on HEK-BlueTM hTLR4 cells with the help of QUANTI-Blue assay and MTS assay. Selected compound 3 was analyzed for its molecular docking with TLR4 by using Autodock vina 1.1.2. Its effect on the TLR4 pathway related cytokines was also evaluated in THP-1 cells and human peripheral blood mononuclear cells by using real-time PCR, ELISA and western blot. Result: Five compounds were synthesized and characterized for effectiveness based on 3,4-dihydropyrimidinone. Compound 3 was found to be the potent hybrid between the synthesized compounds, with high TLR4 inhibition activities and low cytotoxic activities against HEK-BlueTM hTLR4 cells. Molecular docking analysis showed that two hydrogen bonds between compound 3 and residues Asp209(TLR4) and Asp99(MD-2) mainly contribute to the TLR4 inhibition. In addition, compound 3 suppressed LPS-induced of the mRNA expression of TLR4, IP-10, TNF-α, IL-6, IL-12A, and IL-12B, the protein expression of pIRF3 and pNFκB and the secretion of IP-10, TNF-α in THP-1 cell line. Compound 3 also inhibited LPS-induced expression of TNF-α, IL-6, and IL-1β but increased IP-10 at mRNA levels in human peripheral blood mononuclear cells. Conclusion: Our study reveals compound 3, a novel 3,4-dihydropyrimidinone derivative, is a potential TLR4 antagonist, which opens up new research avenues for the development of promising therapeutic agents for inflammatory and autoimmune diseases.